The markets on non-timber forest products in the humid forest zone of Cameroon - Ndoye, O.; Ruíz Pérez, M. (1997)
Many rural dwellers depend on non-timber forest products (NTFPs) for their livelihood and their income needs. Increased urbanisation (as a result of rural urban migration) is an important factor that expands the size of local markets of NTFPs. This paper focuses on local markets in the humid forest zone of Cameroon and on market intermediaries who facilitate the corrdination (or the matching) of supply and demand of NTFPs by providing market outlets for farmers and guaranteeing a source of domestic supply NTFPs for consumers. The behaviour constraint and standard operating procedures of market intermediares are not always known, especially in the wake of the economoic crisis. Traders of NTFPs do not always deal with a single NTFP. This strategy helps them cross-subsidise among different NTFPs. This means that the margin obtained by selling a particular NTFP can be used to support other NTFPs (purchases, storage, processing). The quantity of NTFPs marketed in the humid forest zone of Cameroon is important. Furthermore, the marketing margins obtained by traders vary between 16% (for Dacryodes edulis) and 30.4% (for Irvingia gabonensis) of the value of sales. In addition, the marketing margins received by those trading in Dacryodes edulis, Ricinodendron heudelotii, and Irvingia gabonensis were higher than the minimum wage in most markets. Thus the study confirmed the role of NTFPs as a source of employment and income for traders and suggests the need for developing these markets.